Investigating the Vagueness Markers and Gender Representation in News Media: A Case Study of Articles Related to COVID-19 - Mozaheb, Mohammad Amin; Morsali, Farhad; Rahimian, Mohammad javad; Rahimzadeh, Ghasem (International Journal of Linguistics, Literature and Translation, 2022)
This paper examines the use of vagueness markers in different news agencies' articles. The articles which are selected as the corpus of this study were related to the coronavirus. In order to examine this issue, 119 articles were randomly selected among nine news agencies. After analyzing the data, the paper finds out that the vagueness markers were used in different news articles, but the most markers used in CNN news agency the related frequency for CNN agency is 94. The Guardian news agency has the lowest number of markers, just 1). Among the markers considered in this paper, More or Less has the highest frequency (157) and sort of had the lowest (2). In the case of gender, it must be noted that women with a frequency of 77 had the highest frequency of using vagueness markers in the news articles. This value for men is 50. According to the paper's findings, we can conclude that the women are more interested in using vagueness markers in their writing.